2016
DOI: 10.1038/ncomms10342
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoscale visualization of functional adhesion/excitability nodes at the intercalated disc

Abstract: Intercellular adhesion and electrical excitability are considered separate cellular properties. Studies of myelinated fibres, however, show that voltage-gated sodium channels (VGSCs) aggregate with cell adhesion molecules at discrete subcellular locations, such as the nodes of Ranvier. Demonstration of similar macromolecular organization in cardiac muscle is missing. Here we combine nanoscale-imaging (single-molecule localization microscopy; electron microscopy; and ‘angle view' scanning patch clamp) with math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 66 publications
6
88
1
3
Order By: Relevance
“…Because smaller Na V 1.5 clusters have been linked to reduced functionality, the observed decreased cluster size at the LM of failing myocytes readily explains the reduction in I Na measured within this region 28. The reduction in I Na amplitude recorded at the LM using the macropatch method was larger than the observed reduction in whole cell current density.…”
Section: Discussionmentioning
confidence: 78%
“…Because smaller Na V 1.5 clusters have been linked to reduced functionality, the observed decreased cluster size at the LM of failing myocytes readily explains the reduction in I Na measured within this region 28. The reduction in I Na amplitude recorded at the LM using the macropatch method was larger than the observed reduction in whole cell current density.…”
Section: Discussionmentioning
confidence: 78%
“…; Leo‐Macias et al . ). A high density of Na + channels was also observed at intercellular contacts in cardiomyocyte cultures (Kucera et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Leo‐Macias et al . ), where, according to most recent estimations, about 50% of Na + channels are located (Lin et al . ; Shy et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we and others demonstrated that Nav1.5 813 and Na + current 14, 15 are enhanced in the intercalated disk (ID). Further, we suggested that the narrow intercellular separation in Nav1.5 rich nanodomains could modulate electrical coupling via localized extracellular ion-mediated effects, also termed ephaptic coupling (EpC) 10, 1618 .…”
Section: Introductionmentioning
confidence: 99%